A Comparative Clinical Study of a Novel Pre-colonoscopy Bowel Capsule Preparation Against Two Commercially Available Liquid Preparations - Kingston-Smith, Harriet; Gunaratne, Anoja W.; Saxon, John; Ramrakha, Sanjay; Dawson, Marie Vic M.; Clancy, Annabel; Wettstein, Antony; Borody, Thomas J. (Frontiers in Medical Technology, 2021)
Background & Aims: Colonoscopy surveillance depends on effective bowel preparation. Inadequate bowel preparation can lead to inaccurate clinical diagnosis, insufficient visualization of the colon and increased risk of missed diagnosis. This study aimed to compare the efficacy and safety of a novel Capsule Bowel Preparation (RitePrep), high-volume (2L) polyethylene glycol electrolyte solution (MoviPrep®) and low-volume (1L) polyethylene glycol electrolyte solution (PlenvuTM). Methods: Patients (n=120) were divided into 3 groups and were administered either RitePrep, MoviPrep® or PlenvuTM as a pre-colonoscopy bowel preparation followed by a colonoscopy at a single centre. Validated Boston Bowel Preparation Score (BBPS) and bubble score were used to evaluate bowel cleanliness. Blood tests were also evaluated. The scores and the blood results were analysed using Kruskal-Wallis and Chi-squared tests. Results: A total of 120 patients (median age of 55; 57 males) (RitePrep (n=40), MoviPrep® (n=40) and PlenvuTM (n=40)) were included in the study. RitePrep was the most effective method for cleansing the bowel, with a significantly higher median BBPS compared to MoviPrep and PlenVu (p= 0.006 and 0.024, respectively). Nearly 50% of the patients in PlenvuTM group showed increased serum osmolarity disturbance. Nausea and vomiting were higher in PlenvuTM and MoviPrep® groups than RitePrep group. Conclusions: RitePrep was demonstrated to be a more effective and safe preparation than the other two preparations. RitePrep was not only well tolerated by all patients; the preparation sufficiently cleared the ascending, transverse, and descending colon, enabling optimal visualization for the clinician. RitePrep was also much safer than the comparators, with no alteration in electrolytes measured. For both the clinician and the patient, RitePrep was the preferred preparation.